Avaliação de processos biológicos enriquecidos em genes variáveis em Tetrapoda e suas linhagens - Thieres Tayroni Martins da Silva (2023)
Tetrapods are an important group of metazoans with a global distribution, occupying different niches and playing various biological roles. They possess various adaptations such as modified limbs that provide distinct forms of locomotion along with complex sensory organs. While most homologous genes are expected to be conserved among species due to purifying selection, genes involved in adaptation processes are often subject to diversifying selection, favoring mutations that alter gene function. In this study, we employed a novel approach in comparative genomics to detect enriched biological processes in variable genes using tetrapod species as a case study, to gain a better understanding of the molecular mechanisms involved in their phenotypic evolution. We downloaded all available complete tetrapod genomes from the NCBI RefSeq and constructed non-redundant proteomes by selecting the longest isoform for each protein-coding gene. We used BUSCO to assess proteome completeness and selected only those with completeness above 80%. We proceeded to use OrthoFinder to establish homology relationships among protein sequences. We utilized MAFFT for multiple sequence alignment, followed by trimAl to calculate alignment identity for each group of homologs. We evaluated only groups containing at least one gene from the model species Homo sapiens or Gallus gallus to explore individual gene annotation and perform enrichment analyses using WebGestalt. As expected, we observed that several housekeeping functions were significantly enriched in conserved genes among the analyzed species. Among the significantly enriched sets of variable genes, we identified various terms and genes related to immune processes, sensory perception, and cytoskeletal components. We conclude that our methodology was capable of identifying enriched categories in variable genes consistent with positive selection analyses, as seen in immune genes, as well as genes potentially undergoing convergent evolution. Additionally, mechanisms of sensory perception appear to have played a crucial role in the diversification of tetrapods.